2022
DOI: 10.3389/fcvm.2022.968184
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and human immunodeficiency virus: A paradigm for epithelial sodium channels?

Abstract: Hypertension is a risk factor for end organ damage and death and is more common in persons with HIV compared to the general population. Several mechanisms have been studied in the pathogenesis of hypertension. Current evidence suggests that the epithelial sodium channel (ENaC) plays a key role in regulating blood pressure through the transport of sodium and water across membranes in the kidney tubules, resulting in retention of sodium and water and an altered fluid balance. However, there is scarcity of inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 213 publications
0
5
0
Order By: Relevance
“…Additionally, it has been suggested ART can synergize with other factors, such as increased glucose, reduced insulin production, and activation of the renin–angiotensin–aldosterone system (RAAS) and increase the activity of the endothelial sodium channel. This process can result in vasoconstriction, increased vascular permeability and activation of innate cells, which have also been linked to the development of hypertension [36]. Establishing how different ART regimens may impact BP changes can inform antihypertensive medication choices, such as using angiotensin‐converting enzyme inhibitors (ACEIs) or ARBs to counteract the possible ART‐induced RAAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been suggested ART can synergize with other factors, such as increased glucose, reduced insulin production, and activation of the renin–angiotensin–aldosterone system (RAAS) and increase the activity of the endothelial sodium channel. This process can result in vasoconstriction, increased vascular permeability and activation of innate cells, which have also been linked to the development of hypertension [36]. Establishing how different ART regimens may impact BP changes can inform antihypertensive medication choices, such as using angiotensin‐converting enzyme inhibitors (ACEIs) or ARBs to counteract the possible ART‐induced RAAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, almost all PWH with hypertension have salt sensitivity [ 46 ]. Although the effects of HIV on ENaC are not well understood, we recently showed that SSBP is more prominent in PWH [ 72 ], and hypothesized that ENaC contributes to vascular dysfunction in this patient population [ 73 ▪ ]. Novel therapeutic targets specific for ENaC of immune cells may ameliorate vascular dysfunction in PWH.…”
Section: Targeting Epithelial Sodium Channel In Specific Patient Groupsmentioning
confidence: 99%
“…Thus, altered ENaC function as a mediator of hypertension in PLHIV remains a hypothesis for now, requiring additional studies. 154…”
Section: Niwaha and Byrdmentioning
confidence: 99%